PENGARUH PRESTASI BELAJAR MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN (PKK) DAN EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 2 PEKANBARU - Lisdayanti Lisdayanti; Sumarno Sumarno; Hardisem Syabrus (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to determine the effect of learning achievement in creative products and entrepreneurship (PKK) subjects and self-efficacy on students' interest in entrepreneurship in SMK Negeri 2 Pekanbaru. The population in this study were students of SMK Negeri 2 Pekanbaru with a total of 836 students and a sample of 89 students obtained from a purposive sampling technique then simplified using the Slovin formula. The characteristics that are considered in sampling with purposive sampling technique are student who are or have completed PKK subjects at SMK Negeri 2 Pekanbaru class XII. Data collection techniques in this study used questionnaires for primary data namely variables of self-efficacy variables and entrepreneurial interest and documentation for secondary data, namely the variable of PKK learning achievement. The data collected was then tabulated and analyzed using multiple linear regression with the help of SPSS 23. The results showed learning achievement PKK subjects and self-efficacy had a positive effect on student interest in entrepreneurship in SMK Negeri 2 Pekanbaru with a regression equation of 23,270 + 0.513 X1 + 0, 456 X2 and contributed 58.3% to students' interest in entrepreneurship.Keywords: Prestasi Belajar, Mata Pelajaran Produk kreatif dan Kewirausahaan, Efikasi Diri, Minat Berwirausaha